2019
DOI: 10.3855/jidc.11099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors for shock and death from E. coli bacteremia in pediatric hematological patients

Abstract: Introduction: The aim of our study was to evaluate the epidemiology, clinical features and risk factors for shock and mortality from Escherichia coli bacteremia among children and adolescents with hematological disorders. Methodology: A retrospective observational study of E. coli bacteremia in the hematology department at Xiangya Hospital from January 2013 to June 2018 was conducted. Clinical characteristics, laboratory results and antimicrobial susceptibility were analysed. Risk factors for shock and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…In our study cohort, the rate of shock was 22.3%, which is a little higher than that reported in studies of adult patients with cancer or hematological diseases 35,36 . However, a previous study reported a rate of 51.1% for shock in pediatric hematological patients with E coli BSIs 37 . In present study, we found that adult was a protective factor for shock, which may also proved that children were more vulnerable to shock.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In our study cohort, the rate of shock was 22.3%, which is a little higher than that reported in studies of adult patients with cancer or hematological diseases 35,36 . However, a previous study reported a rate of 51.1% for shock in pediatric hematological patients with E coli BSIs 37 . In present study, we found that adult was a protective factor for shock, which may also proved that children were more vulnerable to shock.…”
Section: Discussioncontrasting
confidence: 64%
“…BSIs. 37 In present study, we found that adult was a protective factor for shock, which may also proved that children were more vulnerable to shock. However, because the number of patients included in this study is relatively small, so these results require further studies with larger size in different regions to verify.…”
Section: F I G U R Esupporting
confidence: 66%
“…In the last years, the emergence and diffusion of MDR E. coli have been observed. In a trial performed in children with onco-hematological disorders, Wang et al reported that the frequency of septic shock was 51.1%, higher than the average rate of 5–30% in studies of patients of all ages [ 37 ]. Despite the advent of potent antibiotics, P. aeruginosa infection is one of the most serious nosocomial infections related with high mortality in patients with immunosuppression or comorbidities, including FN [ 38 , 39 ].…”
Section: Etiology Of Infections In Febrile Episodesmentioning
confidence: 99%
“… 5 And in China, one study showed that in 45 episodes of E. coli bacteremia, the 30-day all-cause mortality was 22.2%. 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 And in China, one study showed that in 45 episodes of E. coli bacteremia, the 30-day allcause mortality was 22.2%. 6 β-lactams are commonly used in the treatment of BSI caused by E. coli. β-lactamase production remains the most important contributing factor to β-lactam resistance.…”
Section: Introductionmentioning
confidence: 99%